Antiplatelet activity of Lampaya medicinalis Phil. in human platelets - Paulina Ormazabal; Lyanne Rodriguez; Adrián Paredes; Glauco Morales; Eduardo Fuentes; Iván Palomo (NFS Journal, 2022)
Herbal preparations can have beneficial effects to counteract cardiovascular diseases (CVD). Inhibition of platelet aggregation have been shown to be effective in CVD treatment. Medicinal plants contain beneficial compounds that could be a useful source of dietary phytochemicals. In this study, it was evaluated whether the hydroethanolic extract of Lampaya medicinalis Phil. (HEL) and two of its components, genipin and picein, are capable of reducing human platelet aggregation and whether such effect could be associated with the reduction of platelet activation markers. HEL significantly inhibited platelet aggregation stimulated with ADP and TRAP-6 (58 and 80%, respectively). The antiplatelet potential of HEL was reached from 250 μg/mL and at 1000 μg/mL when TRAP-6 and ADP, respectively, were used as agonist. The extract also inhibited GPIIb/IIIa activation at the highest concentration tested (1000 μg/mL). On the other hand, genipin at 20 μM significantly reduced P-selectin expression and GPIIb/IIIa activation, while picein decreased P-selectin expression as well as GPIIb/IIIa activation at 10 μM and 50 μM, respectively. Lampaya medicinalis Phil. might be a good candidate for cardiovascular protection, however further studies are needed to elucidate the mechanism by which this extract inhibits antiplatelet activity.